PENGARUH PENGKOORIDINASIAN KERJASAMA DAERAH TERHADAP EFEKTIVITAS PEMANFAATAN BARANG MILIK DAERAH DALAM RANGKA PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN SUMEDANG - Yeyet Yulianti (JRPA - Journal of Regional Public Administration, 2019)
This research aims to obtain data and information on the Effect of Coordinating Regional Cooperation on the Effectiveness of Utilization of Regional Property in the Context of Increasing Regional Revenue in Sumedang Regency. In this article, what is discussed is about the coordination of regional cooperation, such as what is the effectiveness of the use of regional property and what kind of increase in local revenue in Sumedang Regency. The method used in this study is a descriptive analysis method, with there are three variables, namely the Coordination of Regional Cooperation as an independent variable, the Effectiveness of Utilization of Regional Property as an intermediate variable, and the Increase in Regional Original Income as the dependent variable. The population in this study was 226 employees in the Regional Government of Sumedang Regency. The number of samples used is based on the Slovin formula with a minimum number of 69 people. The sampling technique used was cluster random sampling with details of 4 Head of Divisions, 12 Head of Subdivisions, and 53 Implementers at the Regional Secretariat. Data collection techniques in this study were by distributing questionnaires containing various statements to respondents. The measuring instrument used in the form of 54 statements relating to three variables. The scale used is a Likert scale. The results of statistical calculations show that the level of Regional Cooperation Coordination is Good that is equal to 82.56, the level of Effectiveness of Utilization of Regional Property is Good which is equal to 81.05%, the level of Increasing Local Revenue is Good that is equal to 81.81%. The correlation between the Coordination of Regional Cooperation, the Effectiveness of Utilization of Regional Owned Goods and the Increase in Regional Original Revenues obtained 0.69 results. Based on research shows that the Coordination of Regional Cooperation (X) has a significant and positive effect on the Utilization of Regional Property (Y) in realizing the Increase of Regional Revenue in Sumedang Regency (Z) by 63.90%, while the rest (PYZ) 2 is 14.10% is influenced by other variables outside the variable Effectiveness of Utilization of Regional Property and Increased Local Revenue in Sumedang Regency which is not included in the model.